CHAPTER 12.2 IDENTIFICATION AND QUANTITATIVE ANALYSIS OF CLAY MINERALS - Środoń J. (My University, 2006)
This chapter discusses clay mineral identification and quantification and reviews the corresponding literature. Quantitative analysis is most often performed to obtain percentages of clay minerals either in the bulk rock or in the clay fraction. XRD is the most commonly used technique, but IR spectroscopy and major element analysis, combined with qualitative XRD, were also applied. The identification of clay minerals by X-ray diffraction (XRD) has been described in the literature, three of which are of particular importance and relevance. However, the Mineralogical Society (UK), the Mineralogical Society of America, and the Clay Minerals Society (USA) also published several monographs on techniques of clay mineral analysis and identification. A study described in the chapter concentrates on spectroscopic methods of clay mineral analysis, while that is dedicated to the quantitative analysis of soil clay minerals. Simplified analytical methods have long been able to provide semi-quantitative data. Some techniques recently produced satisfactory quantitative results and further progress is expected in this field.